1990
DOI: 10.1002/jcu.1870180104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation methods for intrauterine growth using neonatal fat stores instead of birth weight as outcome measures: Fetal and neonatal measurements correlated with neonatal skinfold thicknesses

Abstract: Neonatal anthropometry, including timed skinfold measurements, was performed on 55 products of selected pregnancies. These skinfold measurements were compared with published standards of measurements obtained by similar techniques. Values outside the 3rd percentile to 97th percentile range were overlaid on the birth weight/menstrual age relationship of these subjects. Seven of 10 subjects with the lowest midtriceps skinfolds weighed more than 2500 g at birth (2 more than 3500 g) and 2 of 4 with the largest mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…For instance, half of infants with low skinfold thickness measurements have an appropriate birth weight for their gestational age (Owen 1997), demonstratin g that birth weight is less able to detect cases of malnutrition than skinfold thickness. Neonatal subcutaneous fat store is also a better predictor of newborn outcome than birth weight: low skinfold thickness at birth predicts neonatal thermal vulnerability better than did birth weight (Sumners, Findley and Ferguson 1990). Furthermore, neonates with low skinfold thickness in relation to birth weight have lower plasma glucose levels (Oakley and Parsons 1977).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, half of infants with low skinfold thickness measurements have an appropriate birth weight for their gestational age (Owen 1997), demonstratin g that birth weight is less able to detect cases of malnutrition than skinfold thickness. Neonatal subcutaneous fat store is also a better predictor of newborn outcome than birth weight: low skinfold thickness at birth predicts neonatal thermal vulnerability better than did birth weight (Sumners, Findley and Ferguson 1990). Furthermore, neonates with low skinfold thickness in relation to birth weight have lower plasma glucose levels (Oakley and Parsons 1977).…”
Section: Introductionmentioning
confidence: 98%
“…Owen et al (2002) found that half of newborns with a suitable weight for their GA had low skinfold thickness (SK) values. The SK measurements have been more closely related to early metabolic alterations and neonatal evolution than to weight (Sumners et al 1990;Oakley and Parsons 1977). Therefore, the SK measurement has been proposed to provide more accurate information on fetal nutrition than simple weight (Sumners et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The SK measurements have been more closely related to early metabolic alterations and neonatal evolution than to weight (Sumners et al 1990;Oakley and Parsons 1977). Therefore, the SK measurement has been proposed to provide more accurate information on fetal nutrition than simple weight (Sumners et al 1990). This is a simple method to assess the neonatal subcutaneous fat stores, and this method has been validated in newborns (Schmelzle and Fusch 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing more accurate information on fetal nutrition than simple weight, skinfold thickness measurements are widely used in the assessment of nutritional status throughout the life course, and offer a fast and non-invasive method of examining body fat mass particularly in newborns. 9,10 A study by Catalano et al 11 that examined 188 singleton term neonates showed that neonatal fat mass constitutes 14% of total birth weight but, explains nearly half of the variance in normal birth weight. Clearly, birth weight cannot be taken as a full proxy marker for neonatal adiposity, and a better understanding of the determinants of adiposity is required.…”
Section: Introductionmentioning
confidence: 99%